2002
DOI: 10.1097/00024382-200211000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Potentiated Hepatic Microcirculatory Response to Endothelin-1 During Polymicrobial Sepsis

Abstract: We conducted this study to elucidate the role of endothelins (ET-1) in mediating the hepatic microcirculatory dysfunction observed in response to sepsis. Following 24 h of cecal ligation and puncture (CLP), we performed intravital microscopy both in vivo and on isolated perfused livers. Portal resistance increased in response to ET-1 in both sham and septic rats, with no significant difference between the two in either in vivo or in isolated livers. Sinusoidal volumetric flow (Qs) was evaluated using red blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 22 publications
6
39
0
Order By: Relevance
“…Recent studies indicate that the putative ET B1 receptors mediate the constriction of the hepatic sinusoids, but the effect tends to be masked by the concomitant vasodilatory actions of NO (Higuchi and Satoh, 1997). Along with the increase in ET-1 mRNA, expression of its receptor, ET B , was significantly increased in endotoxemia, which is consistent with other studies that reported a higher ET B receptor proportion during endotoxemia (Baveja et al, 2002). The increase in ET B receptor expression was augmented by GdCl 3 .…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies indicate that the putative ET B1 receptors mediate the constriction of the hepatic sinusoids, but the effect tends to be masked by the concomitant vasodilatory actions of NO (Higuchi and Satoh, 1997). Along with the increase in ET-1 mRNA, expression of its receptor, ET B , was significantly increased in endotoxemia, which is consistent with other studies that reported a higher ET B receptor proportion during endotoxemia (Baveja et al, 2002). The increase in ET B receptor expression was augmented by GdCl 3 .…”
Section: Discussionsupporting
confidence: 88%
“…The increased vascular resistance in the portal circulation is due to a combination of both increased production of ET-1 and an increased vascular responsiveness to ET-1 [38,39]. The increase in portal vein flow in response to tezosentan implies an increased blood flow to the liver, but since we did not measure hepatic artery flow, we could not calculate the total blood flow to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that the disruption of microvascular blood flow during sepsis might contribute to the subsequent development of MODS [3]. Liver microcirculation is normally maintained under the fine balance of vasoconstrictors and vasodilators, of which endothelin-1 (ET-1), nitric oxide (NO), and carbon monoxide (CO) have been reported to be the prominent vasomediators [4].…”
Section: Introductionmentioning
confidence: 99%